Penerapan Mesin Screw Press Gambir pada Kelompok Maju Tani di Desa Boangmanalu Kecamatan Salak Kabupaten Pakpak Bharat - Jandri Fan HT Saragi; Sahat; Suadi; Nelson Manurung; Sondang Beatrix Siahaan; Angga Bahri Pratama (Politeknik Piksi Ganesha Indonesia, 2026)
Pakpak Bharat Regency has great potential in gambier (Uncaria Gambir Roxb.) production, yet low productivity, substandard quality, and limited technology remain major challenges. This community engagement program aimed to improve production capacity and product quality through the implementation of a screw press machine and farmer skill enhancement. The method applied was Participatory Action Research (PAR) involving partners in planning, training, mentoring, and evaluation. Results showed a 15–20% production increase per 100 kg of leaves, reduced moisture content to ≤14%, and more uniform yellowish-brown product quality that meets market standards. Moreover, farmers’ knowledge and skills improved, leading to higher efficiency, increased income, and stronger business independence. This program has a significant impact on farmer empowerment and supports the sustainability of gambier enterprises in Pakpak Bharat.